Ser/estar/viver invisível: avaliando as condições de habitabilidade e informalidade das habitações coletivas precárias de aluguel no bairro Varadouro, João Pessoa-PB - Silva, Camila Coelho (2015)
The deterioration and depreciation process on urban centers, especially in the oldest areas of Brazilian cities, has as a main phenomenon resulting from the multiplication of villages, hives, among other means of collective houses. The relative “invisibility” of precarious collective rental houses (HCPAs) in central areas, with special focus on/specially for the city of João Pessoa, leads to conclusions, sometimes rushed ones, in order to asserting of non-vitality, abandon or even the death of “historical centers”. This job points in another direction when highlights the existence of a high number of collective rental houses in the neighborhood of Varadouro. The objective is to evaluate the relations between living conditions and informality of such ways of housing, through their identification, mapping and characterization (achieved through survey forms and photographic records), as well as semi structured interviews with lessors, lessees, and representatives from PMJP (City Hall of João Pessoa). The hypothesis was investigated that the condition of invisibility of collective rental houses facilitates the establishment of precarious living conditions, which strengthens the condition of informality and consequently the performance of the informal housing rental market, consolidating a vicious circle where such issues are conditional and feed. It was observed that the inserted HCPAs in the neighborhood of Varadouro have poor living conditions on the scale of the housing unit as opposed to urban livability; despite the poor collective rental housing do not offer proven, appropriate living conditions for their tenants, they prefer to safeguard the ease of access, transport means and the proximity of the work, namely, the coordination and integration with its surroundings, the having to live in households located in the outskirts of the city, away from their activities and destinations. The work also showed that the informal housing rental market in Varadouro is fraught with uncertainties and conventions based and balanced from interpersonal relationships of trust-loyalty. Finally, it was found that the relationship between habitability and the informal rental market of HCPAs in Varadouro happens clearly in the way it gives (or not) the maintenance of precarious tenements rentals. Due to the relationship of trust-loyalty and dominance between lessors and lessees, adjustments and improvements of buildings usually are not hired; the habitability of housing units is submissive to these relations, when agreements and disagreements lead to precarity of HCPAs.